2012
DOI: 10.1098/rsbl.2012.0374
|View full text |Cite
|
Sign up to set email alerts
|

The sound of arousal in music is context-dependent

Abstract: These authors contributed equally to this study.Humans, and many non-human animals, produce and respond to harsh, unpredictable, nonlinear sounds when alarmed, possibly because these are produced when acoustic production systems (vocal cords and syrinxes) are overblown in stressful, dangerous situations. Humans can simulate nonlinearities in music and soundtracks through the use of technological manipulations. Recent work found that film soundtracks from different genres differentially contain such sounds. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 14 publications
(16 reference statements)
4
34
0
Order By: Relevance
“…This confirmed our prediction of limbic recruitment, perhaps indicating greater intensity, arousal, and ecological urgency signaled by timbral qualities perceived to be ''noisy'' (Blumstein et al, 2012). Numerous studies have implicated the amygdala in emotion processing (Phelps & LeDoux, 2005)-particularly negative, high arousal emotions such as fear (Noesselt, Driver, Heinz, & Dolan, 2005) and aggression (Beaver, Lawrence, Passamonti, & Calder, 2008)-and the amygdala has been found to be preferentially involved in aversive responses to sound (Blood, Zatorre, Bermudez, & Evans, 1999;Kumar et al, 2012;Scott et al, 1997;Zald & Pardo, 2002).…”
Section: Limbic and Insula Response To Noisy Timbresupporting
confidence: 84%
See 1 more Smart Citation
“…This confirmed our prediction of limbic recruitment, perhaps indicating greater intensity, arousal, and ecological urgency signaled by timbral qualities perceived to be ''noisy'' (Blumstein et al, 2012). Numerous studies have implicated the amygdala in emotion processing (Phelps & LeDoux, 2005)-particularly negative, high arousal emotions such as fear (Noesselt, Driver, Heinz, & Dolan, 2005) and aggression (Beaver, Lawrence, Passamonti, & Calder, 2008)-and the amygdala has been found to be preferentially involved in aversive responses to sound (Blood, Zatorre, Bermudez, & Evans, 1999;Kumar et al, 2012;Scott et al, 1997;Zald & Pardo, 2002).…”
Section: Limbic and Insula Response To Noisy Timbresupporting
confidence: 84%
“…There are ethological reasons to postulate that noisy timbres would elicit a more vehement motor and limbic response than nonnoisy timbres (Blumstein, Bryant, & Kaye, 2012). Noisy timbres possess enhanced salience owing in part to the physical arousal correlated with their production, typically in moments of heightened anger or alarm.…”
Section: Discussionmentioning
confidence: 99%
“…Further, nonlinear phenomena present in film soundtracks have been used to elicit fearful responses in humans (Blumstein, Davitian, & Kaye, 2010). Some singers intentionally incorporate biphonation, subharmonics, and abrupt frequency changes into their vocal performances to add musical effect (Neubauer, Edgerton, & Herzel, 2003), and studies have shown that nonlinearities added to music are emotionally evocative (Blumstein, Bryant, & Kaye, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Musical emotions are studied as communicative signals that are encoded in sound by a performer, then decoded by the listening audience (Juslin and Laukka 2003), for whom hearing music as expressive involves registering its resemblance with the bodily or vocal expressions of such or such mental state (Juslin and Västfjäll 2008). For instance, joyful music is often associated with fast pace and animated pitch contours (as is happy speech), melancholic music with slower and flatter melodic lines and dark timbres (as is sad speech), and exciting music with high intensity and high levels of distortion and roughness (as may be an angry shout) (Juslin and Laukka 2003;Ilie and Thompson 2006;Escoffier et al 2013;Blumstein et al 2012).…”
Section: Introductionmentioning
confidence: 99%